Reveiw of effective data encryption and decryption technique - Sugumar, Ramalingam; S, Tamilenthi; M, Gurunathan (International Multidisciplinary Research Journal, 2012)
The requirements of information security within an organization have undergone two major changes in the last several decades. Before the wide spread use of data processing equipment, the security of information felt to be valuable to an organization was provided primarily by physical and administrative means. The collection of tools designed to protect data and to thwart hacker is computer security. Network security measures are needed to protect data during their transmission. This technique for encryption and decryption process to combine two methods ceaser cipher and transposition cipher, ceaser cipher is one of the substitution techniques. A substitution technique is one in which the letters of plain text are replaced by other letter or by numbers or symbols. if the plaintext is viewed as a sequence of bits, then substitution involves replacing plaintext bit patterns with cipher text bit patterns. The encryption process is two stages first, to convert the given plaintext into cipher text using ceaser cipher text technique, second stage the cipher converted using transposition technique, the final output is cipher text, The Decryption is the reverse process of the Encryption.